NIMG-48. TLR7/8-AGONIST-LOADED NANOPARTICLES REPROGRAM TUMOR-ASSOCIATED MYELOID CELLS FOR EFFECTIVE IMMUNOTHERAPY OF EXPERIMENTAL GLIOMA AND MRI-BASED TREATMENT MONITORING. (12th November 2021) - Pfleiderer, Kira; Turco, Verena; Horvat, Natalie K; Hunger, Jessica; Karimian-Jazi, Kianush; Schregel, Katharina; Brugnara, Gianluca; Nguyen, Duy; Jähne, Kristine; Fischer, Manuel; Alsasa, Abdulrahman; Bunse, Theresa; et al.
Abstract: Drivers of glioblastoma progression include the immunosuppressive tumor microenvironment (TME), dominated by tumor-associated myeloid cells. Therefore, we investigated a new approach targeting the myeloid compartment to reprogram myeloid cells in the TME using a β-cyclodextrin nanoparticle (CDNP) formulation encapsulating the toll-like receptor 7 and 8 (TLR7/8) agonist R848. Biodistribution confirmed specific targeting of CDNP-R848 to tumor-associated macrophages (TAMs) (labeling efficiency: 34.0% ± 22.2%), whereas tumor microglia (5.4% ± 4.4%) and splenic macrophages (13.2% ± 0.7%) revealed less uptake. Interestingly, intravenous application of CDNP-R848 induced strong tumor regression with an overall response rate of 80% (2.5% complete response, 52.5% partial response and 25% stable disease, n=40 mice) in Gl261 syngeneic experimental gliomas, while CDNP vehicle treated animals showed exponential tumor growth (100% progressive disease, n=12 mice). As advanced imaging is essential to monitor intracranial disease and possibly predict response and resistance, we performed high resolution magnetic resonance imaging using ultrasmall iron oxide nanoparticles (USPIO) for macrophage tracking. Increased levels of USPIO uptake in vehicle treated animals compared to CDNP-R848 treated animals were found as an early marker of responding mice (ΔT2*: -11.7 ± 4.2 vs -4.0 ± 2.8 ms, p=0.01). This correlated with an increased influx of myeloid cells into the TME of vehicle treated animals and showed a strong correlation of macrophage recruitment and USPIO uptake (R 2 : 0.78, p=0.004). Mechanistically, phenotyping of macrophages (CD45 high /CD11b + ) indicated a pro-inflammatory shift of TAMs with an increased infiltration of pro-inflammatory F4/80 + /MHCII + macrophages during CDNP-R848 treatment. Surprisingly, the anti-tumor effect of CDNP-R848 was independent of CD8+ T cells, CD4+ T cells or NK cells during selective depletion experiments. In summary, this work demonstrates the ability of myeloid-targeted therapies to re-shape the tumor microenvironment for an effective immunotherapy of glioma.